Impacts of environmentally relevant concentrations of antibiotic cocktails on the skin microbiome of Eurasian carp (Cyprinus carpio) - Ashley G. Bell; Emma R. Vaughan; Barbara Kasprzyk-Hordern; Jo Cable; Ben Temperton; Charles R. Tyler (Animal Microbiome)
Abstract Background The skin surfaces of fish harbour diverse assemblages of microbes (microbiomes) that play critical roles in host health and disruption of these microbiomes can lead to disease conditions. Antibiotics, widely used in medicine for human and animal health treatments, are increasingly found in waterways and this is a growing concern due to their potential to alter the balance of microbial ecosystems and drive antimicrobial resistance (AMR). The effects of antibiotics on skin microbiomes in fish, however, have been little explored. This study examines how exposure to environmental levels of antibiotics affects the skin microbiomes of Eurasian carp (Cyprinus carpio). Results A 2-week exposure of Eurasian carp to cocktails of five antibiotics (ciprofloxacin, clarithromycin, sulfamethoxazole, trimethoprim, and tetracycline) at concentrations found in the environment resulted in significant skin bacterial community compositional shifts. Applying 16S rRNA amplicon sequencing, we found enrichment of the genus Arcicella (Proteobacteria) and depletion of Sphaerotilus (Bacteroidetes) with limited recovery even after maintaining the fish for a further two weeks in clean (antibiotic-free) water. In the low-antibiotic concentration exposure group, the tank water microbiome assemblages resembled those of the fish skin suggesting similar responses to the antibiotic treatments. Metagenomic analysis observed no increase in antibiotic resistance genes or changes in metabolic pathway abundance, possibly due to the relatively short duration of antibiotic exposure. Conclusion This study highlights that even low-level exposure to chemical mixtures can alter fish skin microbiome compositions, with limited recovery observed after cessation of exposure. These findings warrant further assessments of the long-term effects and functional consequences of these altered microbiomes on fish health, particularly in environments increasingly affected by anthropogenic chemical pollution.